2005
DOI: 10.1002/ppul.20162
|View full text |Cite
|
Sign up to set email alerts
|

Association of body composition and lung function in children with cystic fibrosis

Abstract: Survival in cystic fibrosis has improved significantly in the last 30 years, with major therapeutic goals of delaying the progressive loss of pulmonary function and maintaining normal growth. Dual-energy X-ray absorptiometry (DEXA) was performed in children with cystic fibrosis (CF) to assess both bone mineral density and body composition. We hypothesised that there would be an association between body composition and pulmonary function in children with CF. Fifty subjects with CF (28 males), mean age 12.7 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 26 publications
6
40
0
3
Order By: Relevance
“…A grande maioria de pacientes apresentava insuficiência pancreática, com um impacto quase inevitável no estado nutricional e no crescimento -fatores associados com estado pulmonar e desfecho em FC [21][22][23] . Entre 1986 e 1996, peso médio para idade aumentou significativamente em crianças com FC na África do Sul, aproximando-se dos níveis normais no final dessa década 24 .…”
Section: S Aureusunclassified
“…A grande maioria de pacientes apresentava insuficiência pancreática, com um impacto quase inevitável no estado nutricional e no crescimento -fatores associados com estado pulmonar e desfecho em FC [21][22][23] . Entre 1986 e 1996, peso médio para idade aumentou significativamente em crianças com FC na África do Sul, aproximando-se dos níveis normais no final dessa década 24 .…”
Section: S Aureusunclassified
“…La correlación directa entre VEF 1 e IMC fue signifi cativa, a pesar del tamaño muestral, siendo comparable a la reportada en niños australianos con enfermedad leve 28 . Aún no está claro el mecanismo de esta interacción que probablemente depende de la preservación de masa magra, con mejor contractibilidad de los músculos respiratorios 24,29 .…”
Section: Discussionunclassified
“…(24,25) Analysis of body composition in this group revealed that patients with worse pulmonary function values had a concomitant higher prevalence of muscle mass and fat mass below the 25th percentile. Pedreira et al (26) found a positive association between lean body mass and FEV 1 in CF patients in the 7-17 year age bracket.…”
Section: Resultsmentioning
confidence: 99%